Comparison of the prevalence of Crimean-Congo hemorrhagic fever virus in endemic and non-endemic Bulgarian locations - Ivanka Gergova; Bozhin Kamarinchev (Journal of Vector Borne Diseases, 2013)
Background & objectives: The Balkans is an endemic region for Crimean-Congo hemorrhagic fever (CCHF), caused by the CCHF virus (CCHFV). Several Bulgarian regions comprised of smaller locations are categorized either as endemic or non-endemic for CCHF. However, little is known about the dynamics that underlie the development of endemicity within the locations throughout the years. Methods: Seven locations categorized as endemic in one central Bulgarian region (Stara Zagora) were compared to seven non-endemic areas. During the period 2006-12, a total of 1775 blood samples from cattle, were tested for anti-CCHFV antibodies using an indirect immunofluorescence antibody assay. Also, the infestation of 617 mature ticks for CCHFV was studied using a combination of an immunofluorescence haemocytes assay and molecularvirological methods. Results: Anti-CCHFV antibodies were established in 7.89% (140/1775) of the sera. The average CCHFV-infestation in the ticks was 1.46% (9/617). CCHFV was detected in three tick species: H.m. marginatum (3.73%, 6/161), being the main vector of the infection; R. sanguineus (1.63%, 2/123); and I. ricinus (1.96%, 1/51). Interpretation & conclusion: The data for the endemic and non-endemic locations did not reveal significant differences for the prevalence of CCHFV. Mosaic dispersion of the virus was determined in the studied region and the results did not vary significantly throughout the investigated years.